New definition of the web ontology language OWL2 - Kurgaev, A.F. (Reports of the National Academy of Sciences of Ukraine, 2018)
In the metalanguage of normal forms of knowledge (NFK), we give descriptions of the Manchester syntax and syntax of the functional style of the web ontology language OWL 2 — the central language of the semantic stack by Tim Berners-Lee. The availability of such descriptions guarantees that OWL 2 can be implemented as long as the interpreter of the NFK meta-language is implemented first. It is shown that the expressive capabilities of the NFK meta-language for the description of OWL 2 are quite comparable with the expressive capabilities of the meta-language of Extended Backus-Naur Form.